Care Levels for Fetal Therapy Centers. Issue 6 (2nd June 2022) - Baschat, Ahmet A.; Blackwell, Sean B.; Chatterjee, Debnath; Cummings, James J.; Emery, Stephen P.; Hirose, Shinjiro; Hollier, Lisa M.; Johnson, Anthony; Kilpatrick, Sarah J.; Luks, Francois I.; Menard, M. Kathryn; McCullough, Lawrence B.; et al.
Abstract : Three care levels for fetal therapy centers are proposed based on the resources needed to carry out interventions and manage maternal, fetal, and neonatal risks. Abstract : Fetal therapies undertaken to improve fetal outcome or to optimize transition to neonate life often entail some level of maternal, fetal, or neonatal risk. A fetal therapy center needs access to resources to carry out such therapies and to manage maternal, fetal, and neonatal complications that might arise, either related to the therapy per se or as part of the underlying fetal or maternal condition. Accordingly, a fetal therapy center requires a dedicated operational infrastructure and necessary resources to allow for appropriate oversight and monitoring of clinical performance and to facilitate multidisciplinary collaboration between the relevant specialties. Three care levels for fetal therapy centers are proposed to match the anticipated care complexity, with appropriate resources to achieve an optimal outcome at an institutional and regional level. A level I fetal therapy center should be capable of offering fetal interventions that may be associated with obstetric risks of preterm birth or membrane rupture but that would be very unlikely to require maternal medical subspecialty or intensive care, with neonatal risks not exceeding those of moderate prematurity. A level II center should have the incremental capacity to provide maternal intensive care and to manage extreme neonatal prematurity. A level III therapy center should offer the full range of fetal interventions (including open fetal surgery) and be able manage any of the associated maternal complications and comorbidities, as well as have access to neonatal and pediatric surgical intervention including indicated surgery for neonates with congenital anomalies.